The Effectiveness of Ginger and Turmeric Boiled Water on Milk Production in Postpartum Mothers - Tiara Fatrin; Titin Apriyani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Breast milk is the ideal food for babies. Besides boosting the baby's autoimmune system, making them less susceptible to illness, breastfeeding can also prevent irregular and low milk production. A preliminary study found that some mothers still do not exclusively breastfeed due to irregular or low milk production. To address this issue, an innovation was created in the form of boiled ginger and turmeric water, which is believed to facilitate milk production and increase milk production due to its lactogogum content. The purpose of this study was to identify differences in breast milk production before and after the intervention. This study used a quasi-experimental design with a one-group pre-test-post-test. This study used a checklist data collection technique with direct observation of the administration of boiled ginger and turmeric water on breast milk production in postpartum mothers. The population was 15 postpartum mothers on days 5-7 using purposive sampling. The results of the paired t-test analysis showed an increase in breast milk production, proving that boiled ginger and turmeric water can increase breast milk production and facilitate breast milk production.